2019
DOI: 10.1038/s41467-019-09179-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting glutamine-addiction and overcoming CDK4/6 inhibitor resistance in human esophageal squamous cell carcinoma

Abstract: The dysregulation of Fbxo4-cyclin D1 axis occurs at high frequency in esophageal squamous cell carcinoma (ESCC), where it promotes ESCC development and progression. However, defining a therapeutic vulnerability that results from this dysregulation has remained elusive. Here we demonstrate that Rb and mTORC1 contribute to Gln-addiction upon the dysregulation of the Fbxo4-cyclin D1 axis, which leads to the reprogramming of cellular metabolism. This reprogramming is characterized by reduced energy production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 64 publications
0
60
0
Order By: Relevance
“…A combinatorial strategy may help to overcome glutaminase inhibition resistance. Several inhibitors targeting glycolysis have demonstrated a synergistic effect with glutaminase inhibitor, such as metformin (115,143,144), Erlotinib (EGFR inhibitor) (145), MLN128 (mTOR inhibitor) (52), and Glutor (glucose uptake inhibitor) (146). Co-inhibition of FAO with etomoxir (CPT1 inhibitor) as well inhibits the cell proliferation in resistant cells (130,142).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…A combinatorial strategy may help to overcome glutaminase inhibition resistance. Several inhibitors targeting glycolysis have demonstrated a synergistic effect with glutaminase inhibitor, such as metformin (115,143,144), Erlotinib (EGFR inhibitor) (145), MLN128 (mTOR inhibitor) (52), and Glutor (glucose uptake inhibitor) (146). Co-inhibition of FAO with etomoxir (CPT1 inhibitor) as well inhibits the cell proliferation in resistant cells (130,142).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…This differential regulation of mTORC1 and mTORC2 is mediated by sestrin2 and Glutamine is a versatile molecule, as it serves as an alternative carbon source for energy production and its carbon and nitrogen are also used for biosynthetic reactions [130]. Hence, cancer cells can develop addiction to glutamine and upregulate its metabolism to provide necessary building blocks for the growing tumor [131,132]. mTOR has been linked to the regulation of many of these processes.…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“…For example, Obrist et al conducted mass spectrometric metabolomics and specific interventions on glutamine metabolism and found that glutamine was majorly utilized for nucleotide biosynthesis rather than for bioenergetic, anaplerotic or redox reactions in cisplatin-resistant NSCLC and ovarian cancer cells [74]. The reprogramming of glutaminolysis via the Fbxo4-cyclin D1 axis was reported to contribute to CDK4/6 inhibitor resistance in human ESCC [75]. Disruption of glutamine metabolic pathways could enhance the drug responsiveness of pancreatic cancer to gemcitabine treatment [76].…”
Section: Amino Acid Metabolismmentioning
confidence: 99%